Advanced manufacturing of thermoplastic tape preforms: braiding simulation, curved preforming, and consolidation via rotational and bladder-assisted molding - Eric Mischorr; Patrick Schaible; Veit Würfel; Johannes Keil; Anton Gelencsér; Sebastian Schabel; Jürgen Fleischer; Maik Gude (Advanced Manufacturing: Polymer & Composites Science)
Transportation emissions are a major driver of global warming, making vehicle greenhouse gas reduction essential. Lightweight design, such as hollow shafts and tubes, lowers energy use by optimizing stiffness-to-mass ratios. Fiber-reinforced polymers, especially thermoplastic variants, excel in these applications due to their high specific stiffness, customizable mechanical properties, and scalable manufacturing. This study introduces two novel methods for producing braided hollow carbon fiber-reinforced polyamide 6 profiles: rotational molding for straight preforms and bladder-assisted molding for curved preforms. Numerical simulations of braiding were compared to actual braid architectures, revealing both the capabilities and current limitations of the simulation software for tape-based braiding. Analyses included fiber angle, cover factor, and CT-based wall thickness measurements. The potential for increasing consolidation pressure in rotational molding is shown by means of a theoretical analysis. Bladder-assisted molding produced fully consolidated, minimally wrinkled curved profiles, proving the feasibility of manufacturing high-quality curved braided profiles without post-consolidation forming.